Product Market Competition, Insider Trading, and Stock Market Efficiency - PERESS, JOEL (Journal of Finance, 2010)
ABSTRACT How does competition in firms' product markets influence their behavior in equity markets? Do product market imperfections spread to equity markets? We examine these questions in a noisy rational expectations model in which firms operate under monopolistic competition while their shares trade in perfectly competitive markets. Firms use their monopoly power to pass on shocks to customers, thereby insulating their profits. This encourages stock trading, expedites the capitalization of private information into stock prices and improves the allocation of capital. Several implications are derived and tested.